Patient experiences of an online consultation system: a qualitative study in English primary care post-COVID-19 - Moschogianis, Susan; Darley, Sarah; Coulson, Tessa; Peek, Niels; Cheraghi-Sohi, Sudeh; Brown, Benjamin C (British journal of general practice, 2024)
Online consultation systems (OCSs) allow patients to contact their healthcare teams online. Since 2020 they have been rapidly rolled out in primary care following policy initiatives and the COVID-19 pandemic. In-depth research of patients' experiences using OCSs is lacking. Explore patients' experiences of using an OCS. Qualitative study in English GP practices using the Patchs OCS (www.Patchs.ai) from March 2020 to July 2022. Thematic analysis of 25 patient interviews and 21 467 written comments from 11 851 patients who used the OCS from nine and 240 GP practices, respectively. Patients cited benefits of using the OCS as speed, flexibility, and efficiency. Nevertheless, some patients desired a return to traditional consultation methods. GP practices often did not clearly advertise the OCS or use it as patients expected, which caused frustration. Patients reported advantages of having a written record of consultations and the opportunity to communicate detailed queries in free text. Views differed on how the OCS influenced clinical safety and discussions of sensitive topics. Patients who struggled to communicate in traditional consultations often preferred using the OCS, and male patients reported being more likely to use it. Globally, this is the largest in-depth study of patient experiences of an OCS. It contributes new knowledge that the patient experience of using OCSs can be influenced by previously unreported patient characteristics and the conditions they consult about. Further, it contributes recommendations on the design and implementation of the OCS in practice.